A relationship between sleep quality and academic performance in first-year university students. - Carter, Meagan M. (My University, 2013)
The purpose of this study was to determine whether a relationship existed between sleep quality and academic performance in freshman university students. This study was significant because it is the goal of most universities to assist their students in learning to be successful inside and outside of the classroom. Current research supports a relationship between sleep and academic performance; however few studies are performed utilizing only freshmen as participants. Additionally, this study removed the self-reported variable of grade point average since university registrar's records were accessed to determine the grade point averages for analyses. While it was very weak, a significant negative relationship existed (r=-.145, p=.02) between sleep quality and grade point averages for freshmen at the University of Central Oklahoma.
Keywords: Academic achievement; Sleep; Academic Performance; College Students; Freshmen; GPA; Health; Sleep